Acute Kidney Injury is Associated with Poor Lung Outcomes in Infants Born ≥32 Weeks of Gestational Age - Starr, Michelle C.; Boohaker, Louis; Eldredge, Laurie C.; Menon, Shina; Griffin, Russell; Mayock, Dennis; Askenazi, David; Hingorani, Sangeeta; on behalf of the Neonatal Kidney Collaborative; Ambalavanan, Namasivayam; Selewski, David T.; Sarkar, Subrata; Kent, Alison; Fletcher, Jeffery; Abitbol, Carolyn L.; DeFreitas, Marissa; Duara, Shahnaz; Charlton, Jennifer R.; Swanson, Jonathan R.; Guillet, Ronnie; D'Angio, Carl; Mian, Ayesa; Rademacher, Erin; Mhanna, Maroun J.; Raina, Rupesh; Kumar, Deepak; Jetton, Jennifer G.; Brophy, Patrick D.; Colaizy, Tarah T.; Klein, Jonathan M.; Arikan, Ayse Akcan; Rhee, Christopher J.; Goldstein, Stuart L.; Nathan, Amy T.; Kupferman, Juan C.; Bhutada, Alok; Rastogi, Shantanu; Bonachea, Elizabeth; Mahan, John; Cole, F. Sessions; Davis, T. Keefe; Dower, Joshua; Milner, Lawrence; Smith, Alexandra; Fuloria, Mamta; Reidy, Kimberly; Kaskel, Frederick J.; Soranno, Danielle E.; Gien, Jason; Gist, Katja M.; Chishti, Aftab S.; Hanna, Mina H.; Wong, Craig S.; Joseph, Catherine; DuPont, Tara; Ohls, Robin; Staples, Amy; Khokhar, Surender; Perazzo, Sofia; Ray, Patricio E.; Revenis, Mary; Sethi, Sidharth K.; Rohatgi, Smriri; Mammen, Cherry; Synnes, Anne; Wazir, Sanjay; Wintermark, Pia; Woroniecki, Robert; Sridhar, Shanty; Ingraham, Susan; Nada, Arwa; Zappitelli, Michael (American Journal of Perinatology, 2020)
Objective This study aimed to evaluate the association between acute kidney injury (AKI) and lung outcomes in infants born ≥32 weeks of gestational age (GA).Study Design Secondary analysis of infants ≥32 weeks of GA in the assessment of worldwide acute kidney injury epidemiology in neonates (AWAKEN) retrospective cohort (n = 1,348). We used logistic regression to assess association between AKI and a composite outcome of chronic lung disease (CLD) or death at 28 days of age and linear regression to evaluate association between AKI and duration of respiratory support.Results CLD occurred in 82/1,348 (6.1%) infants, while death occurred in 22/1,348 (1.6%); the composite of CLD/death occurred in 104/1,348 (7.7%). Infants with AKI had an almost five-fold increased odds of CLD/death, which remained after controlling for GA, maternal polyhydramnios, multiple gestations, 5-minute Apgar's score, intubation, and hypoxic–ischemic encephalopathy (adjusted odds ratio [OR] = 4.9, 95% confidence interval [CI]: 3.2–7.4; p < 0.0001). Infants with AKI required longer duration of respiratory support (count ratio = 1.59, 95% CI: 1.14–2.23, p = 0.003) and oxygen (count ratio = 1.43, 95% CI: 1.22–1.68, p < 0.0001) compared with those without AKI.Conclusion AKI is associated with CLD/death and longer duration of respiratory support in infants born at ≥32 weeks of GA. Further prospective studies are needed to elucidate the pathophysiologic relationship.
Keywords: acute kidney injury; acute renal failure; acute lung injury; chronic lung disease; organ crosstalk; neonate